Democracies with preexisting conditions and the coronavirus in the Indo-Pacific: special forum - Croissant, Aurel (The Asan forum, 2021)
Around the globe, democracy is ailing. In the past 15 years or so, an increasing number of democracies worldwide have suffered from gradual erosion and decay. | The Asan Forum
First online: June 06, 2020
Gesehen am 20.04.2021